Catch and size composition of Etroplus suratensis (Bloch, 1790) from the Kumarakom region of Vembanad Lake, India - Bindu, L.; Padmakumar, K. G. (Indian Journal of Fisheries, 2020)
The present study investigated catch and size composition of Etroplus suratensis (Bloch, 1790), based on the data collected from two main fishing practices common in the Vembanad Lake, South India. Both the fishing practices viz., gillnetting and scare line fishing were in vogue round the year and the landings showed considerable variations. E. suratensis constituted 49% of the gillnet landings, while scare line fishing is exclusively for this species. In Kumarakom region of the lake, the estimated annual landings of E. suratensis by scare line and gillnet varied from 14,369 to 30,232 kg and 1,747 to 2,142 kg respectively during the study period. Size distribution studies showed that young ones constituted a significant proportion of gillnet landings, whereas subadults and adult fishes were more in scare line catch. Length-weight relationship showed isometric growth pattern with b values of 2.890 and 2.700 for gillnet and scare line fishing respectively.Keywords: Catch composition, Etroplus suratensis, Gillnet, Scare line, Vembanad Lake